Children’s Rights vis-à-vis the Media: A Study of the Laws of the Republican Era in Afghanistan - A. Basir Mesbah; Sayeed Sulaiman Sadat; Sayed Mohammad Firozi; Ali Juma Hamdard (Journal of Multidisciplinary Law Studies, 2026)
The right of children to access information and media messages is considered one of the important manifestations of children’s rights, and alongside it, their protection and safeguarding against the media is of great importance. After the adoption of the Convention on the Rights of the Child in 1989, national-level laws aimed at protecting children against traditional and new media were developed. Afghanistan, during the two decades of the republican system (2001–2021), in light of the Constitution (2004), enacted the Law on Protection of the Child and the Mass Media Law, which directly or indirectly referred to the rights of this social group in relation to the media. This study employs a comparative legal analysis to examine how Afghanistan’s Republican-era laws protected children’s rights in relation to the media and to evaluate their conformity with the Convention on the Rights of the Child amid limited prior scholarship on Afghan child-media legal protections, has examined and compared the extracted legal codes of these laws with the articles of the Convention on the Rights of the Child.The findings reveal that Afghanistan’s Republican-era legal framework formally aligned with international child rights standards and the Social Responsibility Theory of the press, although significant gaps remained in the practical enforcement of media protections for children. According to our research, the most important axes addressed in the laws of this country were identified as: “the right to freedom of expression,” “the necessity of protecting dignity, reputation, and psychological and moral well-being,” “cultural development,” “the right of access to information,” “protection against immoral content and pornography,” “control of gambling in the online space,” and “prevention of sexual abuse in the dissemination and reception of messages.